(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Different types of plants have been studied for their roles in immunostimulation and treatment of other diseases. The study aimed at evaluating the stimulatory activity of aqueous leaf extract of Cassia occidentalis on innate and adaptive immune responses in mice. Study mice were grouped into five and studied for 21 days; group I (control group) received normal saline. While the treatment groups: group II - V received aqueous leaf extract of C. occidentalis at different concentrations (250, 500, 1000, and 1500) mg/kg body weight (BW). The mice were sensitized and challenged with sheep red blood cells (SRBCs) on day 13th and 18th of the treatment, respectively. On the 19th, 20th, and 21st days, the animals’ delayed-type hypersensitivity (DTH) responses in each group were measured using a digital Vernier calliper, and humoral immune response was evaluated using the haemagglutination (HA) antibody technique. Blood samples were collected for Carbonic particle clearance index (K) and phagocytic index of Macrophage (α). Organ weight index (g/100g) was also recorded (α). The result showed a significant increase in the Carbonic particle clearance index (p=0.02) and phagocytic index of Macrophage (p<0.0001) in a dose-dependent manner. The study revealed a statistically significant difference in HA titres across the five groups, (p=0.02), also the DTH shows a statistically significant difference across the time (24 hours, 48 hours, 72 hours), Wilks’ Lambda = 0. 291, F = 15. 86, p = 0. 0001. The aqueous leaf extract of C. occidentalis has an immunostimulatory effect on innate and adaptive immunity.